1978
DOI: 10.1111/j.1432-1033.1978.tb12419.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Zinc in Poly(A) Synthesis Catalyzed by Nuclear Poly(A) Polymerase

Abstract: The functional role of transition metals in poly(A) synthesis was elucidated by investigating the effect of the metal chelator o-phenanthroline on purified nuclear poly(A) polymerase. This chelator inhibited the enzyme activity in a manner competitive with respect to the polynucleotide primer concentration. o-Phenanthroline was a non-competitive inhibitor with regard to ATP concentration and an 'uncompetitive' inhibitor with regard to dithiothreitol levels. The metal content of the purified enzyme preparations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…RNA polymerase I (9) and poly(A) polymerase (10)(11)(12) were purified to apparent homogeneity from isolated nuclei of the serially transplanted rat tumor, Morris hepatoma 3924A. Purified RNA polymerase I had a specific activity of 125-170 units/mg of protein and exhibited a single Coomassie blue stained band on polyacrylamide gels electrophoresed under nondenaturing conditions (data not shown), which is consistent with our earlier data (9).…”
Section: Methodssupporting
confidence: 86%
“…RNA polymerase I (9) and poly(A) polymerase (10)(11)(12) were purified to apparent homogeneity from isolated nuclei of the serially transplanted rat tumor, Morris hepatoma 3924A. Purified RNA polymerase I had a specific activity of 125-170 units/mg of protein and exhibited a single Coomassie blue stained band on polyacrylamide gels electrophoresed under nondenaturing conditions (data not shown), which is consistent with our earlier data (9).…”
Section: Methodssupporting
confidence: 86%
“…Wells prepared in the absence of enzyme served as controls. In some instances, rat hepatoma poly(A) polymerase, purified as described (19,20), was adsorbed to the wells in place of RNA polymerase I as an additional control. Antisera produced by rabbits immunized with RNA polymerase I (17) efficiently bound to the immobiAbbreviations: SLE, systemic lupus erythematosus; ANA, antinuclear antibody(ies); ENA, extractable nuclear antigens; MCTD, mixed connective tissue disease; RA, rheumatoid arthritis; RNP, ribonucleoprotein; RIA, radioimmunoassay; DBM, diazobenzyloxymethyl.…”
Section: Methodsmentioning
confidence: 99%
“…Poly(A) polymerase was purified from isolated nuclei of Morris hepatoma 3924A (a solid rat tumor) by successive chromatography on DEAE-Sephadex, phosphocellulose, hydroxyapatite, and QAE-Sephadex (8). After QAE-Sephadex chromatography, the enzyme was purified to homogeneity on DNA-cellulose (9). Poly(A) polymerase assays were performed as indicated in ref.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have suggested a role for poly(A) tracts in the stabilization ofmRNA (4), in gene splicing (5,6), and in the formation of the termination codon for translation (7). Studies in our laboratory have shown that nuclear poly(A) polymerase from rat liver and a rat hepatoma differ with respect to the apparent Km for ATP, primer saturation levels, sensitivity to pH changes, molecular weight, amino acid composition (8), zinc content (9), and degree ofphosphorylation (10). Moreover, recent immunological data have demonstrated that hepatoma poly(A) polymerase is much more closely related to the enzyme from other tumors and fetal liver than to the normal liver protein (11).…”
mentioning
confidence: 99%